2020
DOI: 10.7717/peerj.10398
|View full text |Cite
|
Sign up to set email alerts
|

Registered report: investigating a preference for certainty in conversation among autistic adults compared to dyslexic adults and the general population

Abstract: Social communication difficulties are a diagnostic feature in autism. These difficulties are sometimes attributed, at least in part, to impaired ability in making inferences about what other people mean. In this registered report, we test a competing hypothesis that the communication profile of adults on the autism spectrum can be more strongly characterised by reduced confidence in making inferences in the face of uncertain information. We will test this hypothesis by comparing the performance of 100 autistic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
2
1
1

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 36 publications
0
4
0
Order By: Relevance
“…Similar distinctions need to be confirmed in further studies enrolling larger numbers of participants. This is indeed the direction that the literature is taking now, as illustrated for instance in a recent registered report seeking to compare conversational aspects in adults with autism and dyslexia (Wilson & Bishop, 2020).…”
Section: -Conclusionmentioning
confidence: 95%
“…Similar distinctions need to be confirmed in further studies enrolling larger numbers of participants. This is indeed the direction that the literature is taking now, as illustrated for instance in a recent registered report seeking to compare conversational aspects in adults with autism and dyslexia (Wilson & Bishop, 2020).…”
Section: -Conclusionmentioning
confidence: 95%
“…Methods and our analysis plan for this project were published as a registered report ( Wilson & Bishop, 2020b ): https://peerj.com/articles/10398/ . Ethical approval for this project was granted on 30/03/2020 by the Medical Science Interdivisional Research Ethics Committee at Oxford University (Ref: R68518/RE001).…”
Section: Methodsmentioning
confidence: 99%
“…Rules put some order in an otherwise chaotic world. Similarly, A. C. Wilson and Bishop (2020, 2021) suggest that pragmatic difficulties in autism may relate to intolerance of uncertainty (South & Rodgers, 2017). One way to react to such uncertainty is to abide by rules, which provide some safe ground.…”
Section: The Asc Profile and Conventionsmentioning
confidence: 99%
“…This study also found no correlation between reaction times and ToM skills. Recent work by A. C. Wilson and Bishop (2019, 2020, 2021) shows that autistic individuals have problems understanding implicit meanings, such as particularised implicatures, that are not predicted by linguistic skills. Interestingly, they suggest that failures to adequately derive implicatures and sticking to only what is explicitly said may relate to experiencing intolerance of uncertainty (South & Rodgers, 2017), which may give rise to strict adherence to rules.…”
Section: Literalism and Its Explanationsmentioning
confidence: 99%